2015
DOI: 10.3389/fpsyg.2015.01232
|View full text |Cite
|
Sign up to set email alerts
|

Microtiming in Swing and Funk affects the body movement behavior of music expert listeners

Abstract: The theory of Participatory Discrepancies (or PDs) claims that minute temporal asynchronies (microtiming) in music performance are crucial for prompting bodily entrainment in listeners, which is a fundamental effect of the “groove” experience. Previous research has failed to find evidence to support this theory. The present study tested the influence of varying PD magnitudes on the beat-related body movement behavior of music listeners. 160 participants (79 music experts, 81 non-experts) listened to 12 music c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 53 publications
8
77
3
Order By: Relevance
“…Several studies have shown that exposure to music induces a number of physiological and psychological reactions in humans (Blood and Zatorre, 2001;Hodges, 2009;Janata et al, 2012). More particularly, music can induce spontaneous body movement either as simple as tapping and nodding, or as complex as full-body movements (Madison, 2006;Kilchenmann and Senn, 2015;.…”
Section: Music-induced Movementmentioning
confidence: 99%
“…Several studies have shown that exposure to music induces a number of physiological and psychological reactions in humans (Blood and Zatorre, 2001;Hodges, 2009;Janata et al, 2012). More particularly, music can induce spontaneous body movement either as simple as tapping and nodding, or as complex as full-body movements (Madison, 2006;Kilchenmann and Senn, 2015;.…”
Section: Music-induced Movementmentioning
confidence: 99%
“…Kilchenmann and Senn ( 2015 ) addressed the claims of PD theory and the exactitude hypothesis by measuring the actual bodily entrainment response to microtiming manipulations in swing and funk music examples, using video-based motion tracking technology. The data suggest that the timing manipulations had significant effects on the behavior of music expert listeners, while no effects were measured in non-expert listeners.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that most empirical psychological experiments have failed to show that microtiming is positively related to groove does not mean that it is undeserving of the attention given in musicology and ethnomusicology. Rather, as Klichenmann and Senn () have shown, it seems to matter greatly how these rhythmic nuances are implemented, and the conditions under which microtiming is effective have been difficult to recreate in a laboratory setting.…”
mentioning
confidence: 99%